The Oculocardiac Reflex: Its Evolution and Management. Issue 1 (January 2021) - Yoo, Jason J.; Gishen, Kriya E.; Thaller, Seth R.
Abstract : Introduction: The oculocardiac reflex is initiated by a pressure stimulus to the orbit or periorbital structures causing in bradycardia transmitted via the trigeminal-vagus nerve reflex arc. While this most frequently occurs with ophthalmologic surgeries, trauma to the orbit and periorbital structures can result in bradycardia and even in some cases, asystole. The aim of this case report and review of the literature is to identify and examine recent studies of the oculocardiac reflex related to facial trauma and to identify associated patient age, symptoms, and fracture patterns. Methods: A literature search was performed using the database within PubMed.gov using the term "oculocardiac." Results were reviewed for case reports or series related to facial trauma from the year 2000 to 2019. Studies were then evaluated for fracture pattern, presence of entrapment, patient symptoms, and age. Results: The initial search resulted in 109 articles. A total of 22 articles were case reports or series of trauma patients. Twenty articles met inclusion criteria. Median age was 22 years. Eleven patients sustained orbital floor fractures. Four patients sustained medial wall fractures. Three patients had concomitant orbital floor and zygomatic fractures, and 4 with concomitant orbital floor and medial wall fractures. The most common extracardiac symptom experienced was nausea and vomiting (15/23) followed by diplopia (10/23). Status of entrapment was available in 20 patients of which entrapment was reported in fourteen (14/20). Clinical Report: A 26-year old male presents after blunt trauma to the face resulting in a left orbital floor, rim, and maxillary fractures. Extraocular movements were initially intact and the patient had no diplopia. He developed bradycardia to 30 to 40 bpm just prior to induction of anesthesia. He was found to have developed entrapment of the inferior rectus muscle. The orbital floor and rim were repaired with complete resolution of bradycardia. Conclusion: Patients who sustain maxillofacial trauma involving the orbit are at risk of developing the oculocardiac reflex. Patients tend to be younger. The orbital floor is more commonly the site of traumatic injury. Nausea and vomiting are common encountered symptoms. The oculocardiac reflex, clinicians must recognize, is not static but may evolve over a patient's clinical course as seen in our patient. Abstract : Supplemental Digital Content is available in the text